Sport fan satisfaction with the Kansas State Athletic Department’s social media content - Bosco, Kayla (Kansas State University, 2012)
The college sports industry is seeing a change in its marketing strategies with the rise of the popularity of social media. Facebook and Twitter are the two most common social networking sites used by intercollegiate athletic departments. Not only are these outlets used to foster two-way communication with fans, but they are also used as advertising and public relations tools. The purpose of this study is to compare the Kansas State University of Intercollegiate Athletics’ social media objectives and content with the level of satisfaction among representatives of the K-State fan base. Is the athletic department producing the social media content that their fans want to see? In order to gain a better understanding of the nature of the study, in-depth interviews were conducted with various staff members in the K-State Department of Intercollegiate Athletics to determine the social media objectives and to gather their opinions on the content. From there, two focus groups were conducted to ascertain the level of satisfaction among K-State fans with the current content. One group consisted of students while the other group contained K-State alumni. Findings showed that fans were pleased with certain aspects (i.e. score updates on @kstategameday, conciseness of Twitter, videos, etc.) but wanted to see more of other items such as K-State trivia, behind the scenes footage and more on student-athletes. The information gathered was then used to provide suggestions for future social media strategies within the K-State Athletics Department. The recommendations will help to enhance communication with fans and satisfy their social media needs as they relate to K-State Sports.
Keywords: Social media; College sports; Marketing (0338); Mass Communications (0708); Sports Management (0430)